A Brief Overview to Theory of Heights - Tenzer, Robert (Communications - Scientific letters of the University of Zilina, 2002)
In various parts of the world many kinds of height systems have been formulated and practically used in the past. Nowadays, orthometric heights and normal heights are widely used. The orthometric heights are the natural heights above sea level, that is, above the geoid. The definition of the orthometric heights required the knowledge of the topographical masses density distribution between the Earth’s surface and the geoid, at least theoretically. For this reason Molodensky in 1945 formed a theory of normal heights based on the principle that the heights can be evaluated without any hypothesis about the density distribution of topographical masses. Theoretical aspects of the definition of heights are described in this paper.